Inter-and intra-tester reliability of a battery of cervical movement control dysfunction tests. Issue 4 (August 2015) - Segarra, V.; Dueñas, L.; Torres, R.; Falla, D.; Jull, G.; Lluch, E.
Abstract Background Apart from the cranio-cervical flexion test and the deep neck flexor endurance test, evidence related to reliability of cervical movement control dysfunction tests is lacking. Objectives This study investigated the inter- and intra-tester reliability of a battery of cervical movement control dysfunction tests and the effect of clinician experience on reliability in 15 patients with chronic neck pain and 17 non-neck pain controls. In addition, it explored whether impaired performance on this battery of tests was more frequently observed in the neck pain group. Design Inter and intra-tester reliability study. Method Participants were videotaped while performing a battery of nine active cervical movement control dysfunction tests. Two physiotherapists, with different levels of experience, independently rated all tests on two occasions two weeks apart. They were masked to participants' neck pain or non-neck pain status. Results Inter-tester reliability for the complete battery of tests was substantial (κ = 0.69; 95% CI: 0.62, 0.76). Intra-rater reliability values for the expert (κ = 0.86; 95% CI: 0.79, 0.92) and novice (κ = 0.76; 95% confidence intervals (CI): 0.68, 0.84) were overall comparable suggesting that novices can achieve good accuracy with the battery of tests if trained. The frequency of impaired performances in cervical movement control dysfunction tests was low and comparable between groups. Only two tests achieved a greater number of impaired ratings in the patient group. Conclusions Although reliable, further research in larger neck pain populations is required to explore this battery of tests, in order to establish their diagnostic accuracy for identifying clinically relevant cervical movement control dysfunction.